Modeling hurricane-caused urban forest debris in Houston, Texas (2011)
Information on post-hurricane urban forest debris in the Southeastern United States is limited. A stratified subset of permanent plots within the city of Houston, Texas, originally established in 2001 were selected and measured for hurricane impacts on urban forest structure and debris generation following Hurricane Ike which struck the Houston region on September 13, 2008. Three statistical models were developed and input parameters included measured urban forest structure data, land cover data from existing plots, the National Hurricane Center's H*Wind dataset, and the United States Geological Survey's National Land Cover Database. The statistical models estimated tree debris based on alignment of pre- and post-storm data. Land cover was tested as a proxy variable for pre-storm urban forest biomass and post-storm tree debris. Estimates of pre-storm, urban forest biomass were established to test the statistical relationship between pre-storm biomass and poststorm debris. Testing of both land cover as a proxy variable and the biomass–debris relationship were performed to simplify volumetric estimates of debris produced through statistical modeling. Debris models were spatially analyzed to determine debris distribution and to compare with existing literature and available vegetation debris estimation models. Results suggest that urban forest structure variables have greater influence over variation in debris estimates than storm-related variables. Highlights